The Effects of Flexible Manufacturing Capabilities and Logistics Capabilities Upon Organizational Performance: Using Cloud Technology Investment as the Moderator - Lee, Yu-Je; Chen, Ching-Ho (Asian Journal of Empirical Research, 2014)
The purpose of this study is to verify and realize, with the use of Confirmatory Factor Analysis, the interactive effects of cloud technology investment on flexible manufacturing capabilities and logistics capabilities respectively. Research subjects are the section chiefs and managers working at Taiwan-listed photovoltaic companies. The simple Random Sampling method is adopted, and Structural Equation Modeling (SEM) is used to verify the Overall Research Model, and the fitting effect of its Structural and Measurement Models. The results show that having both flexible manufacturing and logistics capabilities provides Taiwan-listed photovoltaic manufacturers’ performance with a significant positive effect, while cloud technology investment also provides a positive interactive effect on a manufacturer’s performance. These results are not only worthy of being the reference for subsequent researchers conducting further research on relevant fields, they can also serve as a reference for sustainable development for business decision-makers of Taiwan-listed Photovoltaic Companies.